Role of the rhizosphere bacterial community in assisting phytoremediation in a lead-zinc area - Xiao, Yunhua; Chen, Liang; Li, Chunxiao; Ma, Jingjing; Chen, Rui; Yang, Bo; Liu, Gang; Liu, Shuming; Fang, Jun (Frontiers in Plant Science, 2023)
Heavy metals (HMs) contamination and vegetation destruction in the mining area caused by mining activities are severely increasing. It is urgent to restore vegetation and stabilize HMs. In this study, we compared the ability of HMs phytoextraction/phytostabilization of three dominant plants, including Artemisia argyi (LA), Miscanthus floridulus (LM), and Boehmeria nivea (LZ) in a lead-zinc mining area in Huayuan County (China). We also explored the role of the rhizosphere bacterial community in assisting phytoremediation. Bioconcentration factor (BCF) and translocation factor (TF) analysis showed that LA preferred accumulating Cd, LZ preferred accumulating Cr and Sb, and LM preferred accumulating Cr and Ni. Significant (p < 0.05) differences were found among the rhizosphere soil microbial communities of these three plants. The key genera of LA were Truepera and Anderseniella, that of LM were Paracoccus and Erythrobacter, and of LZ was Novosphingobium. Correlation analysis showed some rhizosphere bacterial taxa (e.g., Actinomarinicola, Bacillariophyta and Oscillochloris) affected some soil physicochemical parameters (e.g., organic matter and pH) of the rhizosphere soil and enhanced the TF of metals. Functional prediction analysis of soil bacterial community showed that the relative abundances of genes related to the synthesis of some proteins (e.g., manganese/zinc-transporting P-type ATPase C, nickel transport protein and 1-aminocyclopropane-1-carboxylate deaminase) was positively correlated with the phytoextraction/phytostabilization capacity of plants for heavy metals. This study provided theoretical guidance on selecting appropriate plants for different metal remediation applications. We also found some rhizosphere bacteria might enhance the phytoremediation of multi-metals, which could provide a reference for subsequent research.